Behind the scenes: International NGOs’ influence on reproductive health policy in Malawi and South Sudan - and Storeng, Katerini T.; Palmer, Jennifer; Daire, Judith; Kloster, Maren O. (Global Public Health, 2019)
Global health donors increasingly embrace international nongovernmental organisations (INGOs) as partners, often relying on them to conduct political advocacy in recipient countries, especially in controversial policy domains like reproductive health. Although INGOs are the primary recipients of donor funding, they are expected to work through national affiliates or counterparts to enable ‘locally-led’ change. Using prospective policy analysis and ethnographic evidence, this paper examines how donor-funded INGOs have influenced the restrictive policy environments for safe abortion and family planning in South Sudan and Malawi. While external actors themselves emphasise the technical nature of their involvement, the paper analyses them as instrumental political actors who strategically broker alliances and resources to shape policy, often working ‘behind the scenes’ to manage the challenging circumstances they operate under. Consequently, their agency and power are hidden through various practices of effacement or concealment. These practices may be necessary to rationalise the tensions inherent in delivering a global programme with the goal of inducing locally-led change in a highly controversial policy domain, but they also risk inciting suspicion and foreign-national tensions.